Pick the Right Plant - Published by Time-Life Book (Alexandria Time-Life Book)
A gardener's guidebook offers nine hundred entries on plants--which include information on hardiness, height, maintenance, soil, and light needs--for yards with sunlight variations and also features an introduction defining key factors to gardening success.
Include Color Illustrations and Index
Keywords: Plants, Ornamental -- Plants, Ornamental--Selection -- United States